Developing Family Options: Outcomes for mothers with severe mental illness at twelve months of participation. Issue 4 (1st October 2016) - Nicholson, Joanne; Albert, Karen; Gershenson, Bernice; Williams, Valerie; Biebel, Kathleen
ABSTRACT: Family Options is a psychiatric rehabilitation intervention for parents with severe mental illness and their children who work with family coaches to set and achieve goals. The objective of this study is to compare changes in well-being, functioning, and supports and resources achieved from enrollment to 12 months by mothers participating in Family Options ( N = 22) with changes from enrollment to 6 months. Mothers' scores are compared on standardized measures of psychological distress, trauma symptom severity, mental and physical health status, social support, and the number of services needed but not received from enrollment to 6 months, and from enrollment to 12 months. Data were also obtained about help received and satisfaction with Family Options. Mothers achieved significant improvements in well-being at 12 months, as measured in terms of reductions in psychological distress and symptom severity scores. Significant improvements in social support and services received were reported at 6 months but not at 12 months. Mothers received help obtaining services and benefits for themselves and their children and were satisfied with the intervention. Findings underscore the importance of further refinements to the intervention and larger-scale, rigorous testing of Family Options.